ČAS, RAZREZAN NA KOSE (Filološke studije, 2019)
On the grounds of the explanation of hermeneutics I try to interpret Škarje« (Scissors) by Gregor Strniša. Making use of interpretation, yet mostly as destruction, I tried to answer the questions of what is time, what happens with it and the last but not least how its absence influences us. And all this through a dialogue and in giving an answer to the subtitle of the collection Zgodba o času (»A Story about Time«).